2007
DOI: 10.1155/2007/27195
|View full text |Cite
|
Sign up to set email alerts
|

Spectrum of Class wF(p,r,q) Operators

Abstract: Dedicated to Professor Daoxing Xia on his 77th birthday with respect and affectionRecommended by Jozsef Szabados This paper discusses some spectral properties of class wF(p,r, q) operators for p > 0, r > 0, p + r ≤ 1, and q ≥ 1. It is shown that if T is a class wF(p,r, q) operator, then the Riesz idempotent E λ of T with respect to each nonzero isolated point spectrum λ is selfadjoint and* . Afterwards, we prove that every class wF (p,r, q) operator has SVEP and property (β), and Weyl's theorem holds for f (T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 25 publications
0
19
0
Order By: Relevance
“…Theorem 1.2 implies that the structure (same-side and different-side) on powers of p-hyponormal operators for p ≥ 0 always exists. The similar property is proved for more wide classes of operators, see [5,16,27,30,31]. Now, the discussion is focused on the best possibility of the structure.…”
Section: Theorem 11 ([2]) If N Is a Positive Integer And T Ismentioning
confidence: 55%
See 1 more Smart Citation
“…Theorem 1.2 implies that the structure (same-side and different-side) on powers of p-hyponormal operators for p ≥ 0 always exists. The similar property is proved for more wide classes of operators, see [5,16,27,30,31]. Now, the discussion is focused on the best possibility of the structure.…”
Section: Theorem 11 ([2]) If N Is a Positive Integer And T Ismentioning
confidence: 55%
“…This has been generalized to more wide classes of operators [3,28]. Let T be a log-hyponormal operator and n be a positive integer.…”
Section: Applicationsmentioning
confidence: 99%
“…[29]). Recently, some researchers showed that, for some nonnormal operators T , the nonzero points of its point spectrum and joint point spectrum are identical, the nonzero points of its approximate point spectrum and joint approximate point spectrum are identical (cf.…”
Section: Spectrum Of Class A(n)mentioning
confidence: 99%
“…Recently, some researchers showed that, for some nonnormal operators T , the nonzero points of its point spectrum and joint point spectrum are identical, the nonzero points of its approximate point spectrum and joint approximate point spectrum are identical (cf. [3,7,25,29]). In this section, we shall extend this result to class A(n) and show that the spectral mapping theorem on Weyl spectrum holds for class A(n) by using a different method.…”
Section: Spectrum Of Class A(n)mentioning
confidence: 99%
“…It's well known that Furuta inequality has many applications. See [3], [7], [11] and [23]. It has been generalized to grand Furuta inequality and it extended the Ando-Hiai log-majorization theory [8,15,22].…”
Section: Theorem 11 ([4]) Ifmentioning
confidence: 99%